Enhanced solid-state plasmon catalyzed oxidation and SERS signal in the presence of transition metal cations at the surface of gold nanostructures. Issue 38 (22nd September 2021) - Pal, Srimanta; Paul, Sujay; Chattopadhyay, Arun
Abstract : Cartoon depiction of photochemical conversion of 4-ATP into DMAB in the presence and in the absence of metal cations on the surface of Au nanostructures. Abstract : The effect of several metal cations (Mn 2+, Co 2+, Ni 2+, Cu 2+ and Zn 2+ ) on the photochemical conversion of 4-aminothiophenol (4-ATP) into 4, 4′-dimercaptoazobenzene (DMAB) is probed using surface enhanced Raman scattering (SERS). The coupling reaction is carried out on the surface of Au nanoparticles and Au nanorods using 532 nm and 632.8 nm laser excitations, respectively, in the absence and presence of metal cations. Here, we report that DMAB formation on the surface of Au nanostructures – when carried out in the solid state – is augmented significantly (by a factor of 1.98 to 4.07 and 3.34 to 5.74 for Au nanoparticle and Au nanorod substrates, respectively, and depending on the metal). Furthermore, the SERS signal is also markedly enhanced. Thus, the results underpin a new way of carrying out a photochemical reaction with a higher yield along with a higher SERS signal.